Robustness analysis and design of fractional order Iλ Dμ controllers using the small gain theorem. Issue 3 (3rd March 2020) - Azarmi, Roohallah; Tavakoli-Kakhki, Mahsan; Fatehi, Alireza; Sedigh, Ali Khaki
ABSTRACT: In this paper, a simple method is proposed to tune the parameters of Fractional Integral-Fractional Derivative (FIFE) I λ D μ controllers based on the Bode diagram. The proposed technique provides a practical approach for tuning FIFE controllers to compensate stable plants. Using the small gain theorem and based on the sensitivity functions analysis, it is proved that by applying the designed FIFE controller the robustness of the compensated system in the presence of plant uncertainties is improved in comparison to the PI controller in a similar structure. Moreover, the closed-loop phase margin and gain crossover frequency are adjustable by tuning the free controller parameters. Simulation results are presented to demonstrate the simplicity of application and effectiveness of the tuned controller.